Molecular Dynamics Simulations Reveal the Interaction Fingerprint of Remdesivir Triphosphate Pivotal in Allosteric Regulation of SARS-CoV-2 RdRp - Srivastava, Mitul; Mittal, Lovika; Kumari, Anita; Asthana, Shailendra (Frontiers in Molecular Biosciences, 2021)
The COVID-19 pandemic has now strengthened its hold on human health and coronavirus' lethal existence does not seem to go away any sooner. In this regard, the optimization of reported information for understanding the mechanistic insights that may facilitate the discovery of new therapeutics which is an unmet need. Remdesivir (RDV) is a front-line drug to inhibit RNA-dependent RNA-polymerases (RdRp) in distinct viral families including Ebola and SARS-CoV-2. Therefore, its derivatives have the potential to become a broad-spectrum antiviral agent effective against many other RNA viruses. In this study, we performed a comparative analysis between different forms of RDV such as RMP (RDV monophosphate), and RTP (RDV triphosphate) to undermine the inhibition mechanism caused by RTP which is a metabolically active form of RDV. The MD results indicated that RTP rearranges itself towards the NTP entrance site from its initial state which is at the catalytic site, however, RMP stays at the catalytic site only. The thermodynamic profiling and free-energy analysis revealed that a stable pose of RTP seems critical for inhibition as its binding strength improved significantly at NTP entrance site than its initial catalytic site. Also, RTP occupies the residues K545, R553, R555 that are essential to escort NTPs towards the catalytic site, also interacts with other residues D618, P620, K621, R624, K798, and R836 of NTP tunnel that contributes significantly to its stability. From the interaction fingerprinting it is revealed that basic and conserved residues are detrimental for the RdRp activity as RTP perturbed the catalytic site and blocked the NTP entrance site considerably. Overall, we are highlighting the RTP binding mode and key residues that render the SARS-CoV-2 RdRp inactive, paving crucial insights for the discovery of potent inhibitors.